Strain rate dependence of Ti64: Characterisation of mechanical properties up to failure using novel optical techniques - Arthington, M; Siviour, C; Petrinic, N; Elliott, B (EDP Sciences, 2009)
Two methods for the improved characterisation of anisotropic materials are presented. One method utilises three optical videos of cylindrical specimens undergoing uniaxial loading to reconstruct elliptical cross-sectional contours. This information can be used to improve knowledge of anisotropic plastic deformation behaviour. A second method uses digital images of specimens to perform the task of a video extensometer. Through the high resolution imaging of specimens, the undulations due to machining can be seen in edges detected to sub-pixel accuracy. These edges have unique variations along their length that may be tracked to provide high density strain data without occlusions due to the marking required by other methods. The cross-section reconstruction has been applied to rolled Ti64 at strain rates of ~10-3 s -1 , ~1s-1 and ~103 s -1 in compression and tension experiments. Three views have been obtained using both multiple camera rigs and mirrors. The strain measurement through edge tracking has been applied to specimens loaded at ~10-3 s -1 using high resolution imaging.